2020
DOI: 10.1186/s12909-020-02140-2
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study evaluating the integration of a multifaceted evidence-based medicine curriculum into early years in an undergraduate medical school

Abstract: Background: The importance of ensuring medical students are equipped with the skills to be able to practice evidence-based medicine (EBM) has been increasingly recognized in recent years. However, there is limited information on an effective EBM curriculum for undergraduate medical schools. This study aims to test the feasibility of integrating a multifaceted EBM curriculum in the early years of an undergraduate medical school. This was subsequently evaluated using the validated Fresno test and students' self-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…[ 24 ] The integration of the evidence-based medicine (EBM) curriculum was tested for the 1 st year medical students by Kumaravel et al . [ 13 ] and it was shown that the early introduction to EBM principles to medical students before clinical exposure can increase their knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 24 ] The integration of the evidence-based medicine (EBM) curriculum was tested for the 1 st year medical students by Kumaravel et al . [ 13 ] and it was shown that the early introduction to EBM principles to medical students before clinical exposure can increase their knowledge and skills.…”
Section: Discussionmentioning
confidence: 99%
“…[ 5 6 7 ] Several studies have been undertaken regarding the integration of basic and clinical sciences and its effect on education. [ 2 8 9 10 11 12 13 14 15 ] Integration of basic and clinical science courses in U. S. pharmacy programs suggested variations in the design and implementation of integrated courses among U. S. pharmacy programs. [ 2 ] The integration of educational programs in physiopathology courses at Mashhad University of Medical Sciences indicated that integration improves the level of learning in students.…”
Section: Introductionmentioning
confidence: 99%
“…Dessa forma, se faz necessário intervenções e estudos que averiguem a melhor forma de aplicar MBE na grade curricular. (Kumaravel et al, 2020).…”
Section: Fonte: Autores (2022)unclassified
“…Early findings of the evaluation of the curriculum in the initial 2 years have shown it is effective in improving students' EBM knowledge as measured by change in the students' performance in Fresno test [17]. Blended teaching methods have been implemented involving the integration of online and face to face teaching activities.…”
Section: Ebm Curriculum In Ubmsmentioning
confidence: 99%
“…When students move to clinical rotations in their third and fourth years, they are asked to apply their EBM knowledge and skills in real life clinical scenarios. Details of the curriculum along with the evaluation of the effectiveness using validated tools such as the Fresno been described in a previous publication [17]. A spiral approach to the EBM curriculum has been implemented, where teaching of EBM concepts and applications increase in complexity and are reinforced longitudinally throughout the curriculum (Fig.…”
Section: Ebm Curriculum In Ubmsmentioning
confidence: 99%